2021
DOI: 10.1177/1532673x211063215
|View full text |Cite
|
Sign up to set email alerts
|

From Personal Responsibility to Political Mobilization: Using Attribution Frames to Overcome Policy Feedback Effects

Abstract: Public policies that promote personal responsibility while minimizing government responsibility are a key feature of modern American political economy. They can decrease Americans’ political participation on a given issue, with detrimental consequences for the wellbeing of economically insecure families. Can this pattern be overcome? I argue that attribution frames highlighting government’s role in and responsibility for policies may increase people’s propensity for political action on an issue, but only if th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The hollowing out of state usury and fee regulations meant that consumers were left to rely increasingly on federal information disclosures as their primary form of financial protection (SoRelle, 2020). Studies have shown that information disclosures contribute to the privatization of consumer financing as an issue, with negative consequences for political engagement in support of lending reform (SoRelle, 2022a(SoRelle, , 2022b. Thus, by preempting stronger state usury limits, policymakers introduced a feedback process that ultimately made it more challenging to convince borrowers to agitate politically for robust lending protections.…”
Section: Feedback Effects For Organized Interestsmentioning
confidence: 99%
“…The hollowing out of state usury and fee regulations meant that consumers were left to rely increasingly on federal information disclosures as their primary form of financial protection (SoRelle, 2020). Studies have shown that information disclosures contribute to the privatization of consumer financing as an issue, with negative consequences for political engagement in support of lending reform (SoRelle, 2022a(SoRelle, , 2022b. Thus, by preempting stronger state usury limits, policymakers introduced a feedback process that ultimately made it more challenging to convince borrowers to agitate politically for robust lending protections.…”
Section: Feedback Effects For Organized Interestsmentioning
confidence: 99%
“…After observing the relationships among these different attributes and social policy acknowledgement through cross-sectional observational analysis, we test each of the observable implications described earlier through a series of information-based survey experiments. Information treatments have been shown in specific policy contexts to mitigate the effects of the submerged state on a range of political outcomes (e.g., Faricy & Ellis, 2014;Mettler, 2011;SoRelle, 2020SoRelle, , 2022.…”
Section: Data a N D M Et Hodsmentioning
confidence: 99%
“…Because we have a sufficiently large sample size to support the random assignment necessary for a between-subjects design, we have chosen this approach to help alleviate the potential for strategic behavior from opt-in survey takers and to accommodate our information treatments. Between subjects designs like ours are commonly used in feedback research (e.g., Faricy & Ellis, 2014;Mettler, 2011;SoRelle, 2022SoRelle, , 2023.…”
mentioning
confidence: 99%
“…Scholars have found a clear correlation between policy benefits and political engagement (e.g., Campbell 2002), especially when the electorate can link policymaking to a particular governmental actor. The ability to attribute responsibility for policy action is particularly important for consumer lending (SoRelle 2022a), and perhaps especially for student loans, where government’s role has historically been hidden from the public (Mettler 2011). Yet, government’s responsibility for student loan policy was substantially revealed to the public during the highly visible blanket pause on payments and interest during Covid.…”
Section: Study 2: Political Benefits Of Executive Action On Debt Reliefmentioning
confidence: 99%